2003
DOI: 10.1002/ppul.10197
|View full text |Cite
|
Sign up to set email alerts
|

Validation of shuttle tests in children with cystic fibrosis

Abstract: Shuttle tests are simple, inexpensive field tests that have been used to estimate the cardiorespiratory status of children. It has yet to be validated in children with CF. The aim of this study was to assess the reproducibility and criterion validity of shuttle tests in children with cystic fibrosis (CF). Ninety-three CF patients aged 6 to 16 years of age with a wide range of disease severity performed the study. The 10-m shuttle test was used for children 7 years of age and younger and those deemed too chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 14 publications
7
94
1
3
Order By: Relevance
“…[212] compared a 3-min step test with a 6-MWT and found both useful in the assessment of exercise tolerance in children with CF, whereas SELVADURAI et al [213] and POUESSEL et al [214] validated a shuttle test in CF children and found this a useful test.…”
Section: V9o 2 Peak and Ventilatory Indicesmentioning
confidence: 99%
“…[212] compared a 3-min step test with a 6-MWT and found both useful in the assessment of exercise tolerance in children with CF, whereas SELVADURAI et al [213] and POUESSEL et al [214] validated a shuttle test in CF children and found this a useful test.…”
Section: V9o 2 Peak and Ventilatory Indicesmentioning
confidence: 99%
“…The modified shuttle walk test as described by Selvadurai et al (2003) is a symptom-limited exercise test, in which the participant moves from end to end of a 10m course in time with the 'beeps' from a pre-recorded tape. This test is valid in young people with CF (Cox et al, 2006), sensitive to change after hospitalization (Bradley et al, 1999(Bradley et al, , 2000 and correlates with VO 2 max (Rogers et al, 2003).…”
Section: Shuttle Testsmentioning
confidence: 99%
“…It detects improvement in exercise capacity following hospitalization (Pike et al, 2001), but its use may be limited in those with well preserved lung function and fitness levels due to a potential ceiling effect (Selvadurai et al, 2003). It is also clear that actual workload will vary according to step height and weight and height of the participant (Selvadurai et al, 2003).…”
Section: Step Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical performance: Performance was assessed using the Incremental Shuttle Walk Test (ISWT) that is a validated field test of exercise tolerance in CF in which participants walk 10 m lengths at progressively increasing paces [17]. The number of completed shuttles and ISWT distance (ISWD) recorded and used to express exercise tolerance.…”
Section: Measurementsmentioning
confidence: 99%